Bacteremia in a Long Term Care Facility - Le Nicolle; M McIntyre; D Hoban; D Murray (Canadian Journal of Infectious Diseases)
Episodes of bacteremia identified in a long term care facility over a seven and a half-year period from July 1984 to December 1991 were reviewed. Twenty-nine episodes of bacteremia were identified, a rate of 4.35/100,000 patient-days. The most common infecting organisms were Escherichia coli (11 episodes), Streptococcus pneumoniae (four), Proteus mirabilis (three), Staphylococcus aureus (three) and Bacteroides species (two). The source of bacteremia was urinary in 45% of patients, gastrointestinal in 17%, pneumonia in 14%, skin in 14% and unknown in 10%. The overall case fatality rate was 24%, but for the final six years of the review the case fatality rate was only 9.5%. These observations report a rate of bacteremia 10-fold lower than reported from other North American long term care facilities and, potentially, a lower case fatality rate. The primary site of bacteremia, however, in long term care facilities is the urinary tract.